Dental Fear/Anxiety in Children and Child Emotional and Behavioural Problems - Mariana Gonzalez Cademartori; Fernanda Burkert Mathias; Karen Jansen; Marília Leão Goettems (Association of Support to Oral Health Research (APESB), 2023)
Objective: To investigate the association between emotional and behavioural problems and dental fear/anxiety (DFA) in children aged four to 12 years treated at a clinic in southern Brazil. Material and Methods: In this cross-sectional study where mother-child dyads were interviewed, emotional and behavioural problems were investigated using the Strengths and Difficulties Questionnaire (SDQ) (considering five subscales). Children's DFA was evaluated through the Venham Picture Test. For each SDQ subscale, Poisson regression model was explored. Prevalence ratios (PR) were estimated, considering a significant level of p ≤ 0.05. Results: Overall, 128 children participated in this study. Most children were female (54.7%) and aged between 7 and 9 years (39.8%). The prevalence of emotional problems was 47.7% and behavioural problems were 46.1%. The prevalence of DFA was 18.8%. Children with emotional problems had a 2.3 higher prevalence of DFA (95%CI 1.06-5.04). In general, behavioural problems were not associated with DFA (95%CI 0.84-3.34) only when conduct problems were considered (2.20; 95%CI 1.02-4.70). Conclusion: Children aged between 4 and 12 years who present emotional and conduct problems tend to show higher DFA.